Dragonfly dance : poems - Lajimodiere, Denise K. (American Indian studies series (East Lansing, Mich.), 2010)
Dragonfly Dance is a collection of poems remarkable for their candor and sense of catharsis. Writing from the vantage point of an American Indian woman, Denise Lajimodiere opens a door into the lives of Native girls and women. Her poems often reflect the deep tensions between Native culture and white culture. Reflected in Lajimodiere's poems, life is sometimes beautiful but rarely easy. The Necklace, the narrator details how her mother repaired a favorite beaded necklace, her arthritic fingers patiently threading beads on the long thin needle, weaving night after night. When the necklace is finally repaired, she wears it to school where, at recess a boy ran by, yanked it off her neck and threw it. I watched as it ascended high above the blacktop, the beads glittered, scattering their light, a rainbow against gray skies. Unadorned, direct, and often raw, these riveting poems sear their way into our imaginations, inviting us into a world we might never have known. We are richer for the knowledge.